Peran Kepuasan Pelanggan Memediasi Pengaruh Citra Merek Terhadap Niat Beli Ulang Minuman Kopi Kenangan di Denpasar - Kadek Devasya Devi Urmili; I Gst. Ngurah Jaya Agung Widagda K (Journal Of Business, Finance, and Economics (JBFE), 2024)
Repurchase intention is part of consumer behavior where the compatibility between the performance of the product or service offered by the company generates consumer interest to buy again. The development of business in the Food and Beverage industry in Indonesia is increasingly promising. The high consumption of coffee in Indonesia cannot be separated from the current growth trend of coffee shops. Repurchase intention is useful for companies to predict purchase actions that can affect the relationship between brand image and consumer satisfaction. The purpose of this study is to analyze the role of customer satisfaction in mediating the influence of brand image on the intention to repurchase drinks at Kopi Kenangan. The research was conducted on Kopi Kenangan in Denpasar, the number of samples was 120 people using the nonprobability sampling method with purposive sampling techniques. Data collection by questionnaire method is distributed in the form of Google Forms through two ways, namely, online and directly to Kopi Kenangan customers. The collected data was then analyzed using descriptive and inferential statistics (path analysis, classical assumption test, sobel test, and VAF test). Based on the results of the analysis, it was found that brand image has a positive and significant influence on repurchase intention, brand image has a positive and significant influence on customer satisfaction, customer satisfaction has a positive and significant influence on repurchase intention, and customer satisfaction can partially mediate the influence of brand image on repurchase intention. The implications of this result can be used as a marketing development strategy, especially in the management of Kopi Kenangan in Denpasar to pay more attention to brand image indicators and customer satisfaction in order to increase repurchase intentions.